STRUKTUR PASAR BAWANG GORENG VARIETAS LOKAL SUMENEP - Dody Tri Kurniawan; Isdiantoni; Dewi Wulansari (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
The current condition of local fried onion varieties in their marketing activities is still very dependent on middlemen. Producers are very low on market information so they cannot determine for themselves which market channels to use and which are the most efficient, they have not been able to determine prices according to a reasonable margin for them. In addition, the largest production is on orders while the continuous one is very low, because producers do not understand the existing market structure so that their target market information policy is very limited. The purpose of this study is to provide market information to consumers in the form of: Efficient market channels and market margins and information on the structure of the fried onion market. The sample in this study was the Persada Indah Rubaru Cooperative (PIR) with 3 respondents. The analysis used in this study is the analysis of marketing channels and market structure. The analysis of marketing channels includes descriptive analysis for marketing channel patterns. While for the analysis of market structure using market concentration analysis (CR4) and Minimum Efficient Scale (MES). The results of the study showed (1) there are fried onion marketing channels in Mandala Village, namely there is 1 marketing channel, namely the first level marketing channel. Market concentration in the competitive market leads to a perfect competition market with a CR4 value of 35% and an MES value of 9%, which means that market entry and exit barriers are still easy.